2020
DOI: 10.1088/1361-6595/abb41c
|View full text |Cite
|
Sign up to set email alerts
|

Insight into contraction dynamics of microwave plasmas for CO2 conversion from plasma chemistry modelling

Abstract: This work addresses plasma chemistry in the core of a vortex-stabilized microwave discharge for CO2 conversion numerically, focusing on the pressure-dependent contraction dynamics of this plasma. A zero-dimensional model is presented for experimental conditions in a pressure range between 60 and 300 mbar and a temperature range between 3000 and 6500 K. Monte Carlo flux (MCF) simulations, which describe electron kinetics, are self-consistently coupled to the plasma chemistry model. The simulation results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
92
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(111 citation statements)
references
References 82 publications
16
92
3
Order By: Relevance
“…In practice, VT relaxation appears quite important in both MW plasmas (at (sub)atmospheric pressure) and GA plasmas, explaining their high gas temperature (3000 K or higher). For this reason, the CO 2 conversion proceeds mainly by thermal reactions in MW and GA plasmas at practical operating conditions, as demonstrated by several models [271,294,[298][299][300][301][302]. However, Pietanza et al recently studied in detail the kinetics vs thermodynamics effects on CO 2 dissociation in high-temperature MW plasmas, with a self-consistent model of the vibrational kinetics of CO 2 , CO and O 2 , and the electron Boltzmann equation, and they concluded that the assumption of thermodynamic equilibrium in MW CO 2 high temperature plasmas has to be considered with caution, as there are still non-equilibrium effects at play, even at temperatures of 3500-5500 K [271].…”
Section: Insights Obtained From 0d Kinetic Models Of Co 2 Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, VT relaxation appears quite important in both MW plasmas (at (sub)atmospheric pressure) and GA plasmas, explaining their high gas temperature (3000 K or higher). For this reason, the CO 2 conversion proceeds mainly by thermal reactions in MW and GA plasmas at practical operating conditions, as demonstrated by several models [271,294,[298][299][300][301][302]. However, Pietanza et al recently studied in detail the kinetics vs thermodynamics effects on CO 2 dissociation in high-temperature MW plasmas, with a self-consistent model of the vibrational kinetics of CO 2 , CO and O 2 , and the electron Boltzmann equation, and they concluded that the assumption of thermodynamic equilibrium in MW CO 2 high temperature plasmas has to be considered with caution, as there are still non-equilibrium effects at play, even at temperatures of 3500-5500 K [271].…”
Section: Insights Obtained From 0d Kinetic Models Of Co 2 Plasmasmentioning
confidence: 99%
“…Despite the fact that the power was initially mainly deposited into the vibrational levels, fast VT transfer caused significant gas heating, and the CO 2 dissociation was revealed to be mainly thermal. Viegas et al applied a 0D model to describe the plasma chemistry in the core of a vortex-stabilized MW CO 2 plasma, focusing on the pressure-dependent contraction dynamics, in the pressure range between 45 and 225 Torr and temperature range between 3000 and 6500 K [301]. The authors self-consistently coupled the plasma chemistry model with Monte Carlo flux simulations to describe the electron kinetics.…”
Section: Insights Obtained From 0d Kinetic Models Of Co 2 Plasmasmentioning
confidence: 99%
“…The Kerogreen project aims to investigate an advanced PtL conversion route from water and captured CO 2 to carbon neutral jet fuel powered by renewable energy sources [3]. In this project, the crucial step of CO 2 activation is tackled by means of CO 2 plasma splitting into CO and O 2 [4,5]. To circumvent product recombination, O 2 is separated by a solid oxide electrolyte cell.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, MCF can potentially be considered as a reference method, faster than conventional MC approaches, for benchmarking popular Boltzmann solvers that are based on the two-term approximation, with the caveat that, as we have shown, each method must operate with its most appropriate optimized set of cross sections. This model has been integrated in a 0-D model for plasma chemical kinetics in [92].…”
Section: Discussionmentioning
confidence: 99%